Genetic and phylogenetic analysis of feline calicivirus isolates in China. (February 2017) - Sun, Yaxin; Deng, Mingliang; Peng, Zhong; Hu, Ruiming; Chen, Huanchun; Wu, Bin
Highlights: Thirteen isolates of feline calicivirus (FCV) were obtained from cats in Wuhan, China. Phylogenetic analysis of ORF2 sequences from Chinese and worldwide isolates of FCV was performed. Most Chinese FCV isolates belonged to genogroup II. Most Chinese FCVs have a close relationship with some Japanese FCV isolates. Abstract: The aim of this study was to determine the genetic diversity of Chinese feline calicivirus (FCV) isolates and their phylogenetic relationship with isolates from elsewhere in the world. Phylogenetic analysis was performed based on the partial open reading frame (ORF) 2 sequences (regions B–F) of 21 Chinese FCV isolates and 30 global isolates. The Chinese isolates included 13 isolates from Wuhan, which were isolated in this study, and eight previously published isolates. Sixteen Chinese isolates and two Japanese isolates formed a distinct phylogenetic cluster. Phylogenetic analysis based on the sequences of the complete genome, ORF1, ORF2 and ORF3 of selected isolates supported the above findings. Genogroup analysis revealed that FCV genogroup II is present in China. These findings suggest that Chinese FCV isolates are closely related to Japanese FCV isolates.